A Review on the Role of Function Landscape in Encouraging the Psychomotor and Cognitive Development of Pre-School Children - Hussain, Mohd Amirul; Kamaruzaman, Mohd Yusof; Raji, Mohd Nazri Abdul; Basri, Azizul Qayyum; Mamat, Abu Bakar; Basir, Jamilah Mohd; Yunos, Mohd Yazid Mohd (Indonesian Journal of Geography, 2025)
Learning from outside of the classroom includes physical activities and self-exploration that help in developing positive children’s psychomotor as well as cognitive. Given that the learning process in childhood is important for the development of physical and cognitive, the activities in the form of physical game and self-exploration deemed to be a natural mean for the age level to develop their talents and creativity potentials. The environmental landscape factor that is conducive, impacts the cognitive and leaning of the early children education. However, it is deemed to be lacking in the execution of out of class activities in Malaysia’s early childhood learning that uses elements of functional landscape aligned with concept of self-exploration through learning environment. The objective of this study is to explore the functional landscape elements in an exploration park to improve children's physical development. In doing so, this study carried out a literature review involving the analysis of documents related to the importance and ability of the landscape to improve children's cognitive development. This action study is also expected to contribute as reference to schools, institutions, and related parties in emphasizing functional landscape elements in the design of learning centre areas outside the classroom.